Exploring the link between farmers' risk aversion and pineapple yield gaps: Evidence from Bangladesh - Tumpa Datta; Md. Rashid Ahmed; K.M. Mehedi Adnan; Md. Shah Alamgir; Subrata Koiry; Prithila Pooja (Journal of Agriculture and Food Research)
Farmers in Bangladesh's hilly regions face various production risks that significantly impact agricultural output and rural livelihoods. This study aimed to evaluate pineapple growers' perceptions of these risks, the yield disparities in their production, and the correlations between these factors. Primary data were collected from 150 pineapple farmers in Sreemangal Upazila, Bangladesh, using a structured questionnaire and a multi-stage sampling strategy. The Stochastic Frontier and Safety-First Models were employed to assess yield gaps and farmers' risk attitudes. The findings revealed that pineapple seedlings are a critical input for boosting output. A significant yield gap in pineapple production was identified, indicating that farmers could enhance productivity by effectively managing production risks. The analysis also showed that a tiny number of farmers exhibited low-risk aversion, highlighting a generally risk-averse attitude among growers. Furthermore, a strong correlation between risk factors and the yield gap was established using the polynomial regression model. The results underscore the need for government intervention through tailored extension services and high-quality farmer targeted training programs on input optimization to address farmers' risk aversion and reduce the yield gap in pineapple production. This research contributes to understanding how risk attitudes influence agricultural productivity and offers insights for improving farming practices in risk-prone regions of Bangladesh.